A Polícia Civil, os casos na Comissão Interamericana de Direitos Humanos e a efetividade dos Direitos Humanos - Travassos, Bárbara Lisboa (2016)
After intitiating my stricto sensu post-graduate Master studies at Pontifícia Universidade Católica I began questioning myself about the cases of the Inter- American Commission, and the Inter-American Court Of Human Rights, and whether there would be any cases mentioning Polícia Civil de São Paulo (São Paulo Civil Police), an institution of which I have been a member for ten years, as Police Comissioner. Therefore, I conducted research about the cases in which Polícia Civil de São Paulo was mentioned in the Inter-American Comission of Human Rights, and from the information gathered came the intent to develop a diagnosis, a database, and a flow chart containing the information. In addition, there also came an interest to propose cases to be studied by Academia de Polícia Civil (Civil Police Academy) in the training courses of new police officers. Likewise, the interest emerged to evaluate new preventive measures to prevent the recurrence of future human rights violations